Consumer Attitudes to the Smart Home Technologies and the Internet of Things (IoT) - Korneeva, Elena; Olinder, Nina; Strielkowski, Wadim (Energies (Basel), 2021)
This paper focuses on the consumer preferences for the so-called “smart homes” (also known as “smart houses”) which represent a novel addition and a product of the on-going digitalization and the deployment of the Internet of Things (IoT). The major scientific contribution of our study is the empirical model build on the data from the online questionnaire conducted with randomly selected respondents (N = 523) from four European Union (EU) countries and Russia. Even though our results are subject to limitations (no Southern of Northern European countries are included in the scope of this research, which might have yielded different results due to the differences in wealth of citizens and climate in comparison to the Central and Eastern European countries or Germany), they demonstrate that the users included in our sample generally feel inclined to the smart homes technologies and perceive them as a plausible means for improving the safety and security of their lives. On the other hand, some respondents from our sample expressed their concerns over the cybersecurity and technology dependence issues associated with smart homes. It is also apparent that younger respondents (aged 16–35) featured in our research are more worried about their personal data being monitored and analyzed (with a pending threat of leakages). All these results are original and constitute an important scientific value-added to the field of research in smart home technologies and their acceptance by the general public. We demonstrate that the further enhancement of smart homes, and the increase of their popularity and affordability among the customers both in the Central and Eastern European countries and beyond, might depend on the development of the smart grids which these smart homes are an integral part of. The reliability of the smart systems constitutes the key element for achieving the satisfaction of the smart homes residents, and hence needs to be achieved and secured in an effective way. This would ensure the right mix and balance of energy security and efficiency for all customers involved in this process.